Pengaruh Manajemen Laba dan Mekanisme Corporate Governance Terhadap Nilai Perusahaan Pada Industri Barang Konsumsi dalam Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2014 -2018 - Henny Rahayu; Rimi Gusliana Mais; Iman S. Suriawinata (Jurnal Ekonomi, 2020)
This research aims to determine the influence of profit management and the mechanism of corporate governance to the value of the company in the consumer goods industry in the manufacturing company listed on the Stock exchange. This research uses the sample of manufacturing Company of consumer goods industry as many as 15 companies listed on the Indonesia Stock exchange with a period of five years that is 2014-20178 and the number of observations 75. This research uses secondary data with data collection techniques using documentation methods from the official website of Indonesia Stock Exchange and authorized and analyzed using Software Eviews version 10. Based on the results of studies that have been done to analyse profit management has no significant influence on the company's value. The mechanism of corporate governance shows in the proxy independent Commissioner has positive effect on the company's value. And the results showed negative results to the mechanism of corporate governance moderate profit management to the value of the company. But identifying increased corporate governance in order to have Independent commissioner's presence in the board of directors reveals more about the opportunistic side of the company's profit management.